Study of Clinical and Demographic Profile of Scrub Typhus Patients Admitted to a Tertiary Care Hospital in Central India - Dahiphle, A. V.; Achliya, Amit; Chhajed, Neel; Rode, Vikram; Bhise, Kasturi (Faculty of Medicine Universitas Padjadjaran, 2024)
Objectives: To study epidemiological characteristics, clinical features, laboratory findings, and clinical outcomes in cases of scrub typhus. Additionally, the study aims to identify the predictors of disease severity.Methods: This cross-sectional study was conducted in the Department of General Medicine at Dr PDM Medical College in Amaravati, India. The study duration was 6 months, from July 2023 to December 2023. All clinically confirmed patients with scrub typhus were evaluated through history, clinical examination, and appropriate laboratory investigations. The clinical and laboratory profiles, hospital course, and outcomes were analyzed. Organ dysfunction upon admission was assessed using the sequential organ failure assessment (SOFA) score.Results: A total of 200 cases were included in the study. The majority of the cases were in the age range of 31-40 years, and most of them were males. The highest number of scrub typhus cases occurred in September. The most common presenting symptoms were fever (81%), followed by nausea (37.5%), generalized weakness (34%), abdominal pain, eschar (21.5%), breathlessness, and cough (21% each), headache (19%), vomiting (15%), and altered sensorium (4.5%). The majority of patients (72.5%) did not experience any complications, while 55 patients (27.5%) developed multi-organ dysfunction syndrome (MODS) as a complication. The mortality rate was 1%.Conclusion: Scrub typhus is a significant cause of acute febrile illness in the Vidarbha region of Maharashtra. It can present with various clinical manifestations, with or without an eschar. Early diagnosis and appropriate treatment of these cases can lead to minimal complications.